Analysis of the level of penalty shooting ability in the futsal team - Juhanis, Juhanis; Badaru, Benny; Hasanuddin, Imran; Sufitriyono, Sufitriyono; Nurulita, Retno Farhana (Universitas Suryakancana, 2023)
This study investigated the level of penalty shooting kick ability of the futsal team in SMA Negeri 3 Bulukumba. this study applied quantitative method investigating the level of penalty shooting ability. Moreover, descriptive is research conducted to determine the existence of the value of an independent variable, either one variable or more (independent) without making comparisons or connecting with other variables. Data collection was obtained from a 6 meter shooting test. The goal is to look carefully at the ability of the players to kick the ball towards the goal (scoring goals), based on the abilities and targets of the players. The tools employed in this study, i.g.: futsal goal, futsal ball, score sheet, rope, form paper, and recorder. As for the population taken, they were all futsal team players at SMA Negeri 3 Bulukumba, totaling 20 people. The research results are outlined in five scopes including (very high, high, medium, low and very low).The results showed that the level of penalty shooting ability of the futsal team of Senior High School 3 Bulukumba was dominant in the medium category. In detail, 1 student (10%) is in the very high category, 4 students (20%) are in the high category, 8 students (40%) are dominate in the medium category, 5 students (25%) are in the low category and 2 students (10%) ) are in the very low category. It can be concluded that the level of penalty shooting ability in the Senior High School 3 Bulukumba futsal team is dominant in the medium category. Key words: Ability level, Penalty Shoot.